Pengembangan Bromfenol Biru dan Bromtimol Biru pada Label Pintar Sensor Kematangan Buah Naga Merah (Hylocereus polyrhizus) (The Development of Bromophenol Blue and Bromothymol Blue on Ripeness Sensor Smart Label on Red Dragon Fruit (Hylocereus polyrhizu - Raden Ayu Rifqa Zainatul Hurriyah; Bambang Kuswandi; Dwi Koko Pratoko (Pustaka Kesehatan, 2017)
The novel on-package color indicator label has been fabricated based on bromophenol blue and mixture between bromophenol blue and bromothymol blue, and tests have been conducted to assess the ripeness of red dragon fruit (Hylocereus polyrhizus). Bromophenol blue (BPB) and mixture between bromophenol blue and bromothymol blue (BTB) were immobilized onto acetate cellulose membrane via adsorption method. The BPB and mixture between BPB and BTB/acetate cellulose membrane as color indicator work based on pH decrease as the volatile organic compounds (e.g. acetic acid). They produced gradually in the package headspace during developing of red dragon fruit. Subsequently, the color of the indicator will change from blue to green for over-ripe indication, which can be visible visually. The results showed that the color indicator could be used to determine the state of ripeness of the red dragon at ambient condition (25±2oC) and chiller condition (4±2oC). The color change of the indicators reflects the pH of headspace of the red dragon packaging. Furthermore, it also in similar trends to the change of several parameters (soluble solids content, pH, texture, sensory evaluation and weight loss) that normally used to characterize the ripeness of red dragon, therefore the indicator can be used for real time visual monitoring of ripeness state of packaged red dragon fruit. Keywords: ripeness indicator, BPB, BTB, red dragon fruit, acetate cellulose membrane